2016
DOI: 10.1136/annrheumdis-2016-eular.1478
|View full text |Cite
|
Sign up to set email alerts
|

FRI0218 Safety of Non Anti-TNF Biologic Agents in Rheumatic Patients with Past Hepatitis B Virus Infection. A Single-Center Real-Life Study

Abstract: BackgroundThe safety of newer non anti-TNF biologic agents [abatacept (ABA), tocilizumab (TCZ) and rituximab (RTX)] in patients with autoimmune rheumatic diseases and past HBV infection [defined as HBsAg(−), anti-HBc(+), anti-HBs(±)] has not been firmly established.ObjectivesTo assess the safety [reactivation of hepatitis B virus (HBV)] of non anti-TNF biologic agents in patients with serologic evidence of past HBV infection in real-life clinical settings.MethodsRetrospective chart review of patients followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The major risk factors of severe infections are higher age, presence and number of comorbidities, 53 severity of RA, 27 increase in glucocorticoid dose, 28,60 history of biologic DMARD treatment, 50,53 and history of severe infection. 19,21 These risk factors could not be used for further analysis because the number of studies reporting the prevalence of risk factors was limited.…”
Section: Discussionmentioning
confidence: 99%
“…The major risk factors of severe infections are higher age, presence and number of comorbidities, 53 severity of RA, 27 increase in glucocorticoid dose, 28,60 history of biologic DMARD treatment, 50,53 and history of severe infection. 19,21 These risk factors could not be used for further analysis because the number of studies reporting the prevalence of risk factors was limited.…”
Section: Discussionmentioning
confidence: 99%
“…Abatacept has been reported to induce HBV reactivation, although its incidence has been inconsistent due to limited studies 6,18,24 . Six previous studies, that included 138 patients with resolved HBV infection who did not receive nucleoside analogue (NA) prophylaxis, found that only 10 patients experienced HBV reactivation during abatacept treatment, with varying incidence rates across the studies (ranging from 0% to 10.3%) 18,20,25–28 . Two large studies reported relatively high reactivation rates.…”
Section: Discussionmentioning
confidence: 99%
“…6,18,24 Six previous studies, that included 138 patients with resolved HBV infection who did not receive nucleoside analogue (NA) prophylaxis, found that only 10 patients experienced HBV reactivation during abatacept treatment, with varying incidence rates across the studies (ranging from 0% to 10.3%). 18,20,[25][26][27][28] Two large studies reported relatively high reactivation rates. In a prospective study from Japan, 3 of 29 HBsAg−/ HBcAb+ RA patients receiving abatacept experienced HBV reactivation (10.3%).…”
Section: Status a N = 27mentioning
confidence: 99%
“…Twelve out of 26 articles also described the incidence of HBV reactivation in HBsAb− and HBsAb+ patients. Countries (number) of the studies were as follows: China (9), 1,3,6,[8][9][10][11][12][13] Italy (7), [14][15][16][17][18][19][20] Japan (6), 2,21-25 Korea (1), 26 Greece (1), 27 France (1), 28 and Multi-national (1). 29 Table 1 displays the basic characteristics of the 26 studies in our meta-analysis.…”
Section: Study Descriptionmentioning
confidence: 99%